Conceptualizing Democracy as Preparation for Teaching for Democracy - Karynne L. M. Kleine; Christina J Lunsmann (Middle Grades Review, 2019)
In this essay, a broad spectrum of the work of influential educational scholars was examined in order to identify crucial components of teaching for democracy. Synthesizing the literature with their experiences as middle level teachers and teacher educators, the authors determined those conceptions that would be most fruitful for moving in-service teachers to enact the more “muscular” concepts that foster civic participation and social justice. This collaboration resulted in the identification of four democratic practices as a foundation for designing a course on teaching for democracy. These included amplification of the voices of historically marginalized people, recognition that those in power must work to meet the needs of those without power, recognition of the advantages of diversity even at the potential expense of efficiency, and collaboration in order to teach for democracy.
Keywords: Teacher Preparation; Democracy; Curriculum